Laser Needle Knife's Effects on Rabbits Cervical Spondylopathy of Vertebral Artery, Fibrinogen, and Blood Viscosity - Huang, Zhenyu; Xie, Siwei; Liu, Fang; Zhang, Ting; Gu, Yiwen (Frontiers in Surgery, 2022)
Objective: In the rabbit model of cervical spondylosis of vertebral artery disease (CSA), from the perspective of vertebral body morphology, fibrinogen and blood viscosity, through a comparative experiment to study the therapeutic mechanism of laser needle-knife. Methods: 40 healthy common grade rabbits were divided into four groups: normal control group, model group, acupuncture group and laser needle-knife group. The normal control group does not establish a CSA rabbit model, the other groups all establish a CSA rabbit model, but they are treated in different ways. CSA model rabbits were treated with acupuncture and moxibustion at “fengchi” and “cervical Jiaji” points, rabbits in the laser needle-knife group were treated with "Aji" points, and the acupuncture points were punctured with the laser needle-knife. The location of the acupuncture points is determined according to the acupoint map of the experimental map. The right vertebroarterial mophology before and after the treatment were analyzed by scanning electron microscope (SEM), fibrinogen (FIB) concentration and blood viscosity were determined using the coagulation method. Results: After treatment, the capillary and micropore hyperplasia in laser needle-knife group were more evident than that in model group. Compared with the normal condition, the rabbits in the model group showed a more abnormal condition, which was manifested by a significant increase in plasma FIB (p <0.01). However, after a few weeks of treatment, the acupuncture group and the laser acupuncture group showed good conditions. Their plasma FIB was similar to the normal group, and there was no significant difference (p>0.05). Acupuncture and laser needle-knife therapy can reduce whole blood viscosity (1/s, 5/s), and that the distinction between the two treatments is not statistically evident. Conclusion: Acupuncture and laser needle-knife can regulate the coagulation and fibrinolysis system in CSA, stimulate capillary and micropore hyperplasia, reduce blood viscosity, and improve blood circulation, which may be one of the therapeutic mechanisms behind laser needle knife treatment of CSA.